At the margins of empire
1 online resource.
Keywords: "Empire building in British India was inseparably tied to the processes of frontier-making and the creation of boundaries. Through a range of complex practices and developments, the constitution of these spaces took shape at various historical conjunctures. The making of these spaces was also shaped by a variety of imperial concerns, including local and global processes, connections, and entanglements. Focusing on the period between the 19th and the early 20th century, this book looks at how the dynamics of frontier and boundary creation were shaped by a variety of agents, institutions, infrastructure and technologies, events, economy, travel, forms of representation, and imperial rivalries. The role of capital, war and violence were also intrinsic to the creation of such spaces. Further, societies in these spaces responded to these processes in various ways. The book examines how they negotiated and mediated these complex developments of modern space-making in multiple ways at the margins of empire. Part of the Empire and Frontiers series, this book will be of interest to researchers and readers of history, anthropology, cultural studies, social and cultural history, frontiers, boundaries and borderland studies, Himalayan studies, and studies of commodities and circulations"-- Provided by publisher.